Optional Past Tense in Wolof - Bochnak, Ryan; Martinović, Martina (My University, 2019)
In this paper, we discuss the interpretation of the past temporal marker oon in Wolof (Niger-Congo; Senegal), in light of recent claims in the literature regarding its status as a so-called “discontinuous past.” We show that the cessation inference associated with oon is a conversational implicature. Thus, oon can receive an analysis as a plain semantic past tense.
Keywords: Wolof; past tense; markers; recent literature